Epistemology of Knowledge in the Perspective of the Quran - Subhan Subhan (International Journal Labs, 2025)
This research aims to examine the epistemology of science from the perspective of the Qur’an, focusing on the sources, methods, and goals of its achievement within the framework of Islamic science. Through the analysis of texts and concepts in the Qur’an as well as the study of classical and contemporary Muslim thinkers, it was found that Islamic epistemology is integrative and hierarchical, combining revelation as the supreme source, reason as an instrument of interpretation, empirical experience as a means of observation, and intuition as a form of inner guidance. This epistemological system does not reject modern science but rather places it in a moral and theological frame that reinforces the meaning of the search for knowledge. The concept of knowledge in Islam is not only cognitive but also moral and spiritual, directed toward the recognition, usefulness, and perpetuation of Allah. The results of this study are expected to contribute to the reconstruction of a monotheism-based scientific paradigm that is able to address the value crisis in modern science and strengthen the foundation of a holistic and meaningful epistemology. In conclusion, the Qur’anic epistemology provides a holistic, value-based paradigm that seeks to address the crisis of meaning in modern science by grounding knowledge in divine guidance and moral responsibility.